A simplified design of the staggered herringbone micromixer for practical applications - Du, Yan; Zhang, Zhiyi; Yim, ChaeHo; Lin, Min; Cao, Xudong (Université d'Ottawa | University of Ottawa, 2010)
We demonstrated a simple method for the device design of a staggered herringbone micromixer (SHM) using numerical simulation. By correlating the simulated concentrations with channel length, we obtained a series of concentration versus channel length profiles, and used mixing completion length Lm as the only parameter to evaluate the performance of device structure on mixing. Fluorescence quenching experiments were subsequently conducted to verify the optimized SHM structure for a specific application. Good agreement was found between the optimization and the experimental data. Since Lm is straightforward, easily defined and calculated parameter for characterization of mixing performance, this method for designing micromixers is simple and effective for practical applications.
Keywords: radiation quenching; mixing; microfluidics; biological fluid dynamics